Permafrost Degradation Diminishes Terrestrial Ecosystem Carbon Sequestration Capacity on the Qinghai-Tibetan Plateau - Liu, Lei; Zhuang, Qianlai; Zhao, Dongsheng; Zheng, Du; Kou, Dan; Yang, Yuanhe (Global Biogeochemical Cycles, 2022)
Effects of permafrost degradation on carbon (C) and nitrogen (N) cycling on the Qinghai-Tibetan Plateau (QTP) have rarely been analyzed. This study used a revised process-based biogeochemical model to quantify the effects in the region during the 21st century. We found that permafrost degradation would expose 0.61 +/- 0.26 (mean +/- SD) and 1.50 +/- 0.15 Pg C of soil organic carbon under the representative concentration pathway (RCP) 4.5 and the RCP 8.5, respectively. Among them, more than 20% will be decomposed, enhancing heterotrophic respiration by 8.62 +/- 4.51 (RCP 4.5) and 33.66 +/- 14.03 (RCP 8.5) Tg C/yr in 2099. Deep soil N supply due to thawed permafrost is not accessible to plants, only stimulating net primary production by 7.15 +/- 4.83 (RCP 4.5) and 24.27 +/- 9.19 (RCP 8.5) Tg C/yr in 2099. As a result, the single effect of permafrost degradation would cumulatively weaken the regional C sink by 209.44 +/- 137.49 (RCP 4.5) and 371.06 +/- 151.70 (RCP 8.5) Tg C during 2020-2099. However, when factors of climate change, CO2 increasing and permafrost degradation are all considered, the permafrost region on the QTP would be a stronger C sink in the 21st century. Permafrost degradation has a greater influence on C balance of alpine meadows than alpine steppes on the QTP. The shallower active layer, higher soil C and N stocks, and wetter environment in alpine meadows are responsible for its stronger response to permafrost degradation. This study highlights that permafrost degradation could continue to release large amounts of C to the atmosphere irrespective of potentially more nitrogen available from deep soils.